Using Google Earth Images to Extract Dense Landslides Induced by Historical Earthquakes at the Southwest of Ordos, China - Peng, Du; Yueren, Xu; Qinjian, Tian; Wenqiao, Li (Frontiers in Earth Science, 2021)
As historical earthquake records are simple, determining the source parameters of historical strong earthquakes over an extended period is difficult. There are numerous uncertainties in the study of historical earthquakes based on limited literature records. Co-seismic landslide interpretation combined with historical documents can yield the possibility of reducing these uncertainties. The dense co-seismic landslides can be preserved for hundreds to thousands of years in Loess Plateau, North China; furthermore, there are notable attribute differences between earthquake landslides and rainfall-triggered landslides. Along the southwestern margin of the Ordos Block, only one severe earthquake has been recorded in the past 3,000 years. The records of "Sanchuan exhaustion and Qishan collapse" provide clues for an investigation of the 780 BC Qishan earthquake. In this study, combined with historical documents, current high-resolution Google Earth images were used to extract historical landslides along the southwestern of the Ordos Block. There were 6876 landslides with a total area of 643 km2. The landslide-intensive areas were mainly distributed along the Longxian-Qishan-Mazhao Fault in the loess valley area on the northeastern side of the fault. Loess tableland and river terraces occur on the southwest side of the fault; dense landslides have not been examined due to the topographical conditions in this area. By analyzing the spatial distribution of historical earthquake damage in this region, comparing the characteristics of rainfall-triggered landslides, and combining existing dating results for bedrock collapse and loess landslides, the interpretation of dense historical landslides can be linked to the Qishan Earthquake. The interpretation results are associated with historical records. Analyses of current earthquake cases show that the distribution of dense landslides triggered by strong earthquakes can indicate the episeismic area of an earthquake. In addition, the non-integrated landslide catalog without small- and medium-scale coseismic landslides can be used to effectively determine the source parameters of historical strong earthquakes and perform quantitative evaluations. This study evaluates the focal parameters of the 780 BC Qishan earthquake based on interpretations of the spatial distribution range of historical landslides as representations of the range of the extreme earthquake zone.